G456(P) To evaluate the impact of the diagnosis and management of a child with type 1 diabetes on parents. (27th April 2016) - McCormick, C; Millar, S
Abstract : Aim: To evaluate parental stressors in relation to parents caring for a child with type 1 diabetes and the impact of these stressors upon parents and the extended family. Based upon the evidence submitted, techniques to enhance parental coping skills and an improved diabetic service were hoped to be implemented. Methods: 250 questionnaires were posted out to parents of children with type 1 diabetes. Each household received two questionnaires to enable both parents to participate. The questionnaire used was the Paediatric Inventory for Parents as recommened by the International Society for Paediatric and Adolescent Diabetes. Following the return of the questionnaires, two focus groups were held, each consisting of between 3 and 7 parents. The purpose of the focus groups was to discuss areas which had scored highly in the questionnaires as profound stressors. Consent was obtained from the parents who participated in the focus groups to enable recording of the discussion. The parents of the focus groups were chosen at random. Ethical approval had been obtained. Results: 123 questionnaires were returned and of these 66 were female, 16 were male and 41 did not specify their gender. The questionnaire divided the questions into four primary categories: communication, medical care, emotional distance and role function. The emotional distance category scored higher than the others and areas raised of concern by parents included feeling helpless and worrying about the future and longterm impact of the illness. The findings of the focus groups reiniterated parental fear regarding their child's future in addition to the pressure and responsibility of providing 24 h care for their child and society's misconceptions regarding type 1 diabetes. In particular, the focus groups highlighted the impact of caring for a child with type 1 diabetes upon parents. Parental sleep patterns and social outgoings had deterioated. Conclusions: Caring for a child with type 1 diabetes has a major physical and emotional impact upon parental wellbeing. Increased attention needs to be given to supporting parental emotional wellbeing including the availability of psychology services.